Strategy for Optimizing the Use of Instagram Social Media Glow Wedding and Event Planner - Suandewi, Ni Kadek Dian; Wirata, I Nengah; Swandewi, Ni Kadek (PT FORMOSA CENDEKIA GLOBAL, 2024)
In this digital age, information technology has changed the way communication and marketing is done. Wedding Organizers like Glow Wedding and Event Planner need to adopt effective strategies to stay competitive in an increasingly competitive market. Advances in technology and the existence of social media platforms such as Instagram, make it very easy for us to obtain information without being limited by distance. This study aims to determine the strategy of optimizing the use of Glow Wedding and Event Planner's Instagram social media. This research is a qualitative research with data collection techniques through interviews, observation and documentation. The analysis technique uses Marketing theory, Marketing Communication, Social Media, Instagram as Social Media and SWOT analysis. From the results of the SWOT analysis that has been carried out on Glow Wedding and Event Planner, it can be seen that the company needs to utilize the use of content calendar to schedule collaboration posts with decoration vendors, photography, videography and other vendors. The company also needs to recruit a content planner or social media admin, then also utilize documentation from collaborations with influencers to attract new audiences and use Linktree to add links to websites, contacts or reservation pages on Instagram Bio.